The Signal Private Group System and Anonymous Credentials Supporting Efficient Verifiable Encryption - Chase, Melissa; Perrin, Trevor; Zaverucha, Greg (ACM CCS 2020, 2020)
In this paper we present a system for maintaining a membership list of users in a group, designed for use in the Signal Messenger secure messaging app. The goal is to support private groups where membership information is readily available to all group members but hidden from the service provider or anyone outside the group. In the proposed solution, a central server stores the group membership in the form of encrypted entries. Members of the group authenticate to the server in a way that reveals only that they correspond to some encrypted entry, then read and write the encrypted entries. Authentication in our design uses a primitive called a keyed-verification anonymous credential (KVAC), and we construct a new KVAC scheme based on an algebraic MAC, instantiated in a group G of prime order. The benefit of the new KVAC is that attributes may be elements in G, whereas previous schemes could only support attributes that were integers modulo the order of G. This enables us to encrypt group data using an efficient Elgamal-like encryption scheme, and to prove in zero-knowledge that the encrypted data is certified by a credential. Because encryption, authentication, and the associated proofs of knowledge are all instantiated in G the system is efficient, even for large groups.
Also presented at RWC 2021: Real World Crypto Symposium